Notes on the Terror Film - Keith Brown (University of Edinburgh, 2006)
The purpose of this paper—perhaps really more a set of somewhat informal notes, in the manner suggested by David Bordwell (28)—is to provide a broad brushstroke picture of the terror film from its beginnings, arguably coeval with cinema itself, to the present. It will be suggested that the terror film may be seen as something of the horror film's repressed double, going beyond horror in terms of what it has to say about the existential realities of—to borrow Hannah Arendt's term—“the human condition” in the 20th Century.